2016
DOI: 10.3329/baj.v19i1.29876
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Soybean Under Different Levels of Phosphorus and Potassium

Abstract: A field experiment was conducted at the Sher-e-Bangla Agricultural University Farm, Dhaka, Bangladesh during December 2013 to April 2014 to evaluate the effect of phosphorus (P0: 0 kg TSP ha-1, P1: 100 kg TSP ha-1, P2: 175 kg TSP ha-1, P3: 250 kg TSP ha-1) and potassium (K0: 0 kg MoP, K1: 60 kg MoP ha-1, K2: 120 kg MoP ha-1, K3: 180 kg MoP ha-1), and their combinations on growth and yield of soybean (Glycine max). Number of nodules plant-1, number of filled pods plant-1, number of seeds pod-1, 1000-seed weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 8 publications
6
17
0
Order By: Relevance
“…The highest number of pods plant -1 (88.42) was recorded with application of 60 kg P ha -1 which was significantly different from other treatments ( Table 1). The results are in agreement with the findings of Khanam et al (2016) who reported that the number of pods plant -1 increased with the increase of phosphorus rate up to a certain limit and then decreased. Different levels of boron fertilizers also significantly influenced the number of pods plant -1 .…”
Section: Number Of Pods Plant -1supporting
confidence: 93%
See 2 more Smart Citations
“…The highest number of pods plant -1 (88.42) was recorded with application of 60 kg P ha -1 which was significantly different from other treatments ( Table 1). The results are in agreement with the findings of Khanam et al (2016) who reported that the number of pods plant -1 increased with the increase of phosphorus rate up to a certain limit and then decreased. Different levels of boron fertilizers also significantly influenced the number of pods plant -1 .…”
Section: Number Of Pods Plant -1supporting
confidence: 93%
“…The highest soybean yield (1.66 t ha -1 ) was produced when the crop was fertilized with 60 kg P ha -1 and the lowest (1.26 t ha -1 ) in control treatment (Table 1). The result was supported by the findings of Khanam et al (2016). Seed yield of soybean varied significantly with different levels of B fertilizer application ( Table 2).…”
Section: Seed Yieldsupporting
confidence: 77%
See 1 more Smart Citation
“…K content was equal to 1.22 meq kg -1 which was a high value. This element promotes nodulation only in the presence of sufficient quantities of phosphorus (Khanam et al, 2016).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…However, the world average yield of soybean was about 2.9 t ha -1 (FAOSTAT, 2018). The reason for low yield rate of soybean is mainly due to use of low yielding varieties and insufficient agronomic management (Khanam et al, 2016). Experimental evidences reveal that soybean is highly responsive to different fertilizers and its yield can be increased remarkably through the judicious fertilization (BARI, 1988;Mohamed, 1984;Kazi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%